2021
DOI: 10.1186/s13020-021-00528-w
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol attenuates lipotoxicity in hepatocytes via activating SIRT3-AMPK mediated lipophagy

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is characterized by ectopic accumulation of triglycerides in the liver. Emerging evidence has demonstrated that lipophagy regulates lipid mobilization and energy homeostasis in the liver. Sirtuin 3 (SIRT3), a mitochondrial NAD+-dependent deacetylase, modulates the activities of several substrates involving in autophagy and energy metabolism. Honokiol (HK) is a natural lignan from the plants of Magnolia genus that exhibits potent liver protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…More red puncta were formed in the mRFP-GFP-LC3 assay, the colocalization of mRFP-LC3 and Nile red (indicated LDs) was increased, the P/O-induced shrinkage in the ratio of LC3-II/LC3-I and Beclin1 level, and the elevation of P62 were all reversed in HK-treated cells in comparison with the control. In addition, the LD fraction was isolated and the enrichment of LC3-II, Beclin1 and decreased P62 were observed in LD fractions rather than in whole cell homogenates after HK treatment, which further confirmed the lipophagy activation [ 90 ]. In another study, the ethanol extract of Cyclocarya paliurus (CPE) was reported to effectively induce lipid clearance associated with increased autophagy.…”
Section: Potential Therapeutic Effects Of Natural Products On Liver D...mentioning
confidence: 85%
“…More red puncta were formed in the mRFP-GFP-LC3 assay, the colocalization of mRFP-LC3 and Nile red (indicated LDs) was increased, the P/O-induced shrinkage in the ratio of LC3-II/LC3-I and Beclin1 level, and the elevation of P62 were all reversed in HK-treated cells in comparison with the control. In addition, the LD fraction was isolated and the enrichment of LC3-II, Beclin1 and decreased P62 were observed in LD fractions rather than in whole cell homogenates after HK treatment, which further confirmed the lipophagy activation [ 90 ]. In another study, the ethanol extract of Cyclocarya paliurus (CPE) was reported to effectively induce lipid clearance associated with increased autophagy.…”
Section: Potential Therapeutic Effects Of Natural Products On Liver D...mentioning
confidence: 85%
“…57 On the other hand, an improvement in the lipophagy pathway was reported as an effective method to alleviate the progression of NAFLD. For example, the effect of honokiol to ameliorate lipotoxicity in hepatocytes was through activating SIRT3-AMPK mediated lipophagy, 58 and P2X7 improved hepatic steatosis by elevating the lipophagy level. 59 Moreover, the effect of NOB on activating lipophagy was reported in some diseases, such as pulmonary fibrosis 60 and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that HKL can regulate lipid metabolism through other mechanisms. Liu et al found that HKL could ameliorate lipotoxicity in hepatocytes by activating SIRT3-AMPK mediated lipophagy (Liu et al, 2021). Additional study suggested that HKL could block fatty acid synthesis by inhibiting sterol Frontiers in Pharmacology frontiersin.org regulatory element-binding protein-1c (SREBP-1c) maturation and the induction of lipogenic proteins, stearoyl-CoA desaturase-1 (SCD-1) and fatty acid synthase (FASN) (Seo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role and mechanism of HKL in treating CKD remain to be determined. Previously, HKL was reported to attenuate lipid accumulation and lipotoxicity in hepatocytes to protect against non alcoholic fatty liver disease (Seo et al, 2015;Liu et al, 2021). In mice with cisplatin-induced acute kidney injury, HKL could improve fatty acid oxidation and renal function and reduce fatty acid deposition (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%